2020
DOI: 10.1080/14613808.2020.1841131
|View full text |Cite
|
Sign up to set email alerts
|

‘This circle of joy’: meaningful musicians’ work and the benefits of facilitating singing groups

Abstract: The complex realities of musicians' portfolio careers highlight the need for research on musicians' wellbeing. Musicians may include community work within their portfolio such as the facilitation of singing groups for health and wellbeing. Until recently, research on these groups has focused primarily on health and wellbeing outcomes for group participants with little discussion of these factors for the facilitators as professional musicians. We recruited eleven facilitators for semi-structured interviews to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…According to Noble and McGrath (2008) , in school contexts learners have a sense of ‘meaning’ when what they do also has an impact on others beyond themselves. In a sense, balancing and sometimes even subordinating the personal needs to the needs of the group and working toward a shared musical goal, as is often the case when making music together, may help gaining a positive perspective on, and gratitude for, your own life ( Forbes and Bartlett, 2020 ). This is where the idea of participatory sense-making, as elaborated by De Jaegher and Di Paolo (2007) , is of interest.…”
Section: Introductionmentioning
confidence: 99%
“…According to Noble and McGrath (2008) , in school contexts learners have a sense of ‘meaning’ when what they do also has an impact on others beyond themselves. In a sense, balancing and sometimes even subordinating the personal needs to the needs of the group and working toward a shared musical goal, as is often the case when making music together, may help gaining a positive perspective on, and gratitude for, your own life ( Forbes and Bartlett, 2020 ). This is where the idea of participatory sense-making, as elaborated by De Jaegher and Di Paolo (2007) , is of interest.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to highlight these results since the experience of singing (choral practice), as a direct musical expression, could improve well-being as pointed out in previous research [ 50 ]. However, this benefit would be selective since an association between the OMSI and negative emotions is observed, which indicates that there is a group of students that is excluded.…”
Section: Resultsmentioning
confidence: 84%
“…Indeed, for there to be a change in epistemological beliefs, very particular conditions are required, where psychological aspects are articulated within a particular context of social interaction [ 71 ]. Without these elements, which largely depend on the learning environment, future teachers may not fully experience well-being in their professional future, as has been reported in recent research related to context of studying singing [ 50 ]. It is important, then, from a didactic point of view, to consider in greater depth the nature of these students’ previous experiences, to strengthen support networks among peers, and to foment equal opportunities for teaching of the arts at school.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, they need to be active in doing their related activities to maintain their identity (Ascenso et al, 2016). Moreover, previous study also reported that individuals who perform facilitating roles in singing groups for some time, have generated identity, suggesting that their work may open opportunities for self-actualization and bring goodness to the members (Forbes & Bartlett, 2020).…”
Section: Work Identity At the Occupational Levelmentioning
confidence: 99%